A reliable sense maintenance scheme by sense holes recognised and self-healing in sensor networks of internet of things. (25th July 2019) - Liu, Jun; Lu, Xu; Wang, Tao
Sense holes recognised and self-healing in sensor networks have important significance for sense performance. Most of the existing researches assumed that the coordinates are known. A distributed reliable sense maintenance scheme by sense holes recognised and self-healing was presented. Firstly, it reduced the required nodes density limit to maintain reliable sense by mathematical analysis. Then, a sense holes recognised algorithm based on the Hamiltonian graph and computation geometry was proposed. It could identify triangular holes and realise a good recognition rate without nodes accurate position. Based on virtual forces strategy, a sense holes self-healing algorithm was presented. Simulation results showed the algorithm was superior to others in energy-balancing. The sense holes recognised algorithm could efficiently and quickly detect sense holes in sensor networks as shown in simulations.